2021
DOI: 10.1111/conl.12847
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the evidentiary basis for ecological cascades with conservation impacts

Abstract: Complex ecological interactions are widely utilized to deliver conservation benefits but their efficacy is often debated. Using a coral reef trophic cascade as an example, we reveal that outcomes can be surprisingly difficult to detect. Even important impacts of marine reserves can go undetected (20% more coral with power < 0.5). This evidentiary challenge is compounded by misinterpretation of "nonsignificant" results as evidence of failed conservation practice. We illustrate a more appropriate analytical appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The role of local management interventionssuch as MPAsin protecting and building the resilience of coral reefs in the face of global climate change has been debated (e.g. [1,38,61]). Resilience-based management approaches for coral reefs aim to protect reefs from local stressors, increase the resistance of reefs to damage during disturbance and/or increase recovery rates of reefs from damage sustained during disturbance [33].…”
Section: Mpas and Climate Changerecommendations For Measuring And Ens...mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of local management interventionssuch as MPAsin protecting and building the resilience of coral reefs in the face of global climate change has been debated (e.g. [1,38,61]). Resilience-based management approaches for coral reefs aim to protect reefs from local stressors, increase the resistance of reefs to damage during disturbance and/or increase recovery rates of reefs from damage sustained during disturbance [33].…”
Section: Mpas and Climate Changerecommendations For Measuring And Ens...mentioning
confidence: 99%
“…While the role of MPAs in improving reef resilience under climate change has been criticised, given the limited evidence for increased recovery rates following bleaching within MPAs (e.g. [1,39]), more recent work has suggested that the limited evidence should be interpreted as a lack of statistical power in ecological monitoring to detect impacts, rather than MPAs having no impact on coral reef resilience [61].…”
Section: Mpas and Climate Changerecommendations For Measuring And Ens...mentioning
confidence: 99%
“…As a result, whereas local resource managers have aspired to an integrated land–sea approach 19 , evidence of its efficacy above either approach in isolation remains wanting and difficult to test. Detecting conservation benefits in highly dynamic ecosystems is challenging 20 , but recent studies have identified salient connections between local conditions and coral reef resistance to and recovery potential following mass bleaching 2 , 11 , 21 23 . Managers therefore require unambiguous targets for the combination of land–sea human impacts they should mitigate to support coral reef persistence under climate change.…”
Section: Mainmentioning
confidence: 99%
“…Coral reef fishes are a salient group of organisms for reef habitats, contributing to their ecosystem function and the provision of key ecosystem services, including nutrient cycling 1 , herbivory to prevent macroalgae proliferation over coral 2 , and cascading trophic effects 3 , 4 , among others. These functions promote coral reef resilience 5 and drive key ecosystem services such as nutrient provision from fisheries 6 , storm protection 7 , and other economic benefits for human livelihoods 8 10 .…”
Section: Introductionmentioning
confidence: 99%